Attributes Influencing Enterprise Propensity in Urban and Rural Sweden - Hans Westlund; Kent Eliasson (European Regional Science Association (ERSA), 2010)
Policies aiming at promoting entrepreneurship are in general formed on national levels, without any consideration to differences between urban and rural areas. Usually cities are provided with better and more modern infrastructure; cities have better supply of physical, financial and human capital and connected services, and cities have a more modern industrial structure in the sense that their shares of growing industry are higher. These circumstances indicate that policies for entrepreneurship, which in general are designed for urban areas, might not work as intended when they are implemented in rural areas. A first step to improving the efficiency of these policies could be to investigate the differences between cities and countryside regarding frequencies and types entrepreneurship. Based on a database containing socio-economic information on all residents in Sweden this paper examines a) The scope and structure of enterprise propensity in urban and rural areas respectively in Sweden. b) The importance of a number of attributes that may have an impact on individuals' propensity to start an enterprise in the two area types. Besides total (active) populations of urban and rural areas, divisions are made in men and women, in age groups and in different manufacturing and service sectors. Variables on individual level being investigated are education, incomes and combination of incomes from various income sources. Variables on regional level being tested are population size and density, centers' population density, average commuting distance, local employment level and demographics and relative density of firms.
Keywords: 330